The effect of phosphotungstic acid and ferrous sulfate mordants towards the enhancement of flower extracts as alternative to hematoxcylin stain / Ummi Syafiqah Abdorahman - Abdorahman, Ummi Syafiqah (2019)
Aqueous extract derived from Hibiscus sabdariffa (Roselle) and Costus woodsonii (Red button ginger) flower were chosen to be used in Papanicolaou stain protocol to counter the problem of limited sources of Hematoxylin. The aim of this study is to identify the most suitable mordant between Phosphotungstic acid (PTA) and Ferrous sulfate (FS) that have the finest result in enhancing the staining ability of both H. sabdariffa and C. woodsonii on the nucleus of the buccal cells. The dyes were extracted from the flower petals by boiling until it reached 100ºC. Qualitative analysis was done by selecting 10 volunteers to evaluate the staining intensities of the nucleus of the cells. From this observation under the microscope, all dyes with and without mordants were able to stain the nucleus. However, cells that have been stained using extracts that were mordanted with Phosphotungstic acid were slightly degenerated and have poor visibility. The quantitative analysis using One-way ANOVA and paired-samples t-test were done on the pH and absorbance of the pure aqueous extracts. Colour intensities were measured in pixels using MIPAR software. The staining quality of the mordanted and non-mordanted natural dyes were compared with the Papanicolaou stain as a gold standard. Qualitative measurement by the independent evaluators was analysed using Weighted-kappa test. Hence, the statistical analysis revealed that dyes mordanted with ferrous sulfate were proven to have better ability in enhancing the staining intensity of extracts from both flowers compared to Phosphotungstic acid. Nevertheless, the dyes from both flowers and Papanicolaou stain were incomparable. But then again, the ability of mordanted dyes and non-mordanted dyes of H. sabdariffa and C. woodsonii to stain the cells were equivalent. In conclusion, ferrous sulfate is the most suitable mordant in enhancing the staining ability of both flower extracts.